International handbook of education for the changing world of work : bridging academic and vocational learning - Maclean, Rupert [Herausgeber]; Wilson, David [Herausgeber]; Chinien, Chris [Herausgeber] (Springer-Verlag, 1970)
This 6-volume Handbook covers in detail all of the latest practice in technical and vocational education and training (TVET). It provides information on TVET models that occur in different parts of the world. It reflects best and innovatiive practice, and, wherever possible, uses case studies as examples. The Handbook also deals with questions that arise from the shift in the global labour marketplace, especially: How can changes in the labour market be anticipated? How to respond to the dilemma of providing appropriate educational and training courses in a fluid world economy? (BIBB-Doku)
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 2.3.4 Qualifikationswandel; L 2.1.1 Informelles Lernen; S 4.1 Finanzierungsquellen; P 3.2 Lehrpersonal; L 1.3 Curriculumentwicklung; G 2.2 Informations- / Wissensgesellschaft; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; I 2.3.4 Asien; I 2.3.2 Nordamerika; I 2.3.1 Afrika; I 2.3.5 Australien, Ozeanien; Berufsbildungssystem; Arbeitswelt; Arbeitsanforderungen; Qualifikationswandel; Lernen und Arbeiten; Lernen am Arbeitsplatz; Informelles Lernen; Bildungsfinanzierung; Bildungspersonal; Professionalisierung; Curriculumforschung; Curriculumentwicklung; Informationstechnische Bildung; Medieneinsatz; Beziehung Bildungssystem Beschäftigungssystem; Durchlässigkeit im Bildungssystem; Kompetenz; Anerkennung; Nationaler Qualifikationsrahmen; Europa; Asien; Amerika; Afrika; Australien